Effect of arsenic treatments on the element content of green peas - Várallyay, Szilvia; Balláné Kovács, Andrea; Soós, Áron; Kovács, Béla (Acta Agraria Debreceniensis, 2017)
The agricultural environment is contaminated with heavy metals and other toxic elements, which means more and more threats. One of the most important toxic element is the arsenic (As).The objective of the study was to investigate the effect of As-treatments on the element content of the different parts of the green peas (root,stem, leaf, pod, pea) in the 4. phase of the plant development. Plants were grown in green house. Arsenic was applied in a form of arsenate (As[V]) and the plants were treated with 0, 3, 10, 30, 90 and 270 mg kg-1 arsenic.According to the results the Ca content of root and pod was increased in the case of the 3 mg kg-1 As-treatment, after that decreasing tendency was observed. In the case of the 270 mg kg-1 As-treatment, the Ca content in the root was increased, because some element is able to concentrate in the lower biomass. The Ca-content of stem and leaves was reduced when the plants were treated with more than 30 mg kg-1 As. The lowest As-treatment (3 mg kg-1) increased the Na content in the root, stem and leaves, however in the case of the higher As-dose, decreasing tendency was observed. In the case of the generative plant parts the 3 mg kg-1 As-treatment also increased the Na content, nevertheless in the case of the higher As-treatments lower Na content was measured, however in the case of the highest As-treatment (270 mg kg-1) the Na content was increased in the generative plant parts, probably the Na was concentrated in the lower biomass. In the case of the 90 and 270 mg kg-1 As-treatment the Mo-content also was increased in the generative plant parts. The 270 mg kg-1 As-treatment caused a similar tendency in the case of the generative plant parts as a result of the lower biomass. In the case of the pod and leaves, the lower As-doses did not cause significant changes.The Mo content was increased in the root and pea when the plants were treated with 3 mg kg-1 As, but in the case of the higher treatments it was decreased. In the case of the stem it was reverse, the lowest As-tretament (3 mg kg-1) decreased, nevertheless the further As-doses increased the Mo content.